Evaluating the Reliability of COVID-19 Messages from Health Care Providers via the Line Application in the COVID-19 Situation - Srisai, Saowapha (International Journal of Social Sciences: Current and Future Research Trends, 2022)
The COVID-19 infection is a new disease which has spread to all countries of the world. People are worried and concerned about this disease. Thai people regularly send news or messages to their relatives and other people by social media, especially the Line application. Health care providers also influence their patients’ behavior through such messaging. To evaluate the reliability of the COVID-19 messages from health care providers via the Line application and assess the factors that influence the reliability of the messages. A quantitative cross-sectional study was conducted on 99 health care providers in a Thai government hospital. Data were collected using face-to-face interviews. Each interviewee was asked to evaluate 3 COVID-19 messages which they had sent to other people on the Line application. Each message was evaluated for reliability which was assessed based on the criteria of existing web-based evaluation services. Descriptive and logistic regression analysis were performed using the R Program. The prevalence of the participants with 3 high reliability messages was 15.15%. In total there were 297 messages of which only 122 met the criteria for reliable messages (41%). The participants with reliable messages had a significantly higher rate of sending messages from news updates than the other groups. There are many messages on social media, and health care providers need to learn about the reliable messages and consider their impact on others before they make the decision to send messages to others or believe these messages.